1971
DOI: 10.1159/000157902
|View full text |Cite
|
Sign up to set email alerts
|

Responsiveness of the Terminal Vascular Bed in Fast and Slow Skeletal Muscles to <i>α</i>-Adrenergic Stimulation

Abstract: In the light of known differences in bio-chemical, histological, and biophysical characteristics of fast and slow muscle, it was thought feasible to investigate possible differences in vascular properties. The present study has shown that vascular reactivity to α-adrenergic stimulation by both topical application of catecholamines (epinephrine and norepinephrine) and reflex activation of sympathetic nerves, is graded in both fast and slow muscles from precapillary sphincters which are the most sensitive, to sm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
20
2

Year Published

1972
1972
2011
2011

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 20 publications
(24 citation statements)
references
References 5 publications
(5 reference statements)
2
20
2
Order By: Relevance
“…In vivo animal studies have shown that vasoconstrictor responses to sympathetic nerve activation or a-adrenoceptor stimulation are larger in quiescent fast-twitch muscles than in quiescent slow-twitch muscles [6,7,12]. The distribution of slow-twitch fibers/ fast-twitch fibers in able-bodied humans, calculated on the basis of data from various studies cited by Saltin et al [18], is approximately 50/50 in both BB and MG muscles.…”
Section: Hb/mbo 2 Responsementioning
confidence: 99%
“…In vivo animal studies have shown that vasoconstrictor responses to sympathetic nerve activation or a-adrenoceptor stimulation are larger in quiescent fast-twitch muscles than in quiescent slow-twitch muscles [6,7,12]. The distribution of slow-twitch fibers/ fast-twitch fibers in able-bodied humans, calculated on the basis of data from various studies cited by Saltin et al [18], is approximately 50/50 in both BB and MG muscles.…”
Section: Hb/mbo 2 Responsementioning
confidence: 99%
“…The adult pattern, described in a previous report [6], encompasses a range of sensitivities for arterioles in fast muscle which is several orders of magnitude greater than comparable vessels in slow muscle. In adult biceps femoris and medial gastrocnemius the smallest vessels (prccapillary) respond to threshold constrictor doses of 2x l()_5/tg/ml of norepinephirine, whereas small arterioles ( < 20 ¡nm dia meter and larger arterioles (20-40 t/m diameter) needed 2 x 10"4 and 2 x l 0 -*/fg/ml, respectively, to produce minimal effects.…”
Section: Discussionmentioning
confidence: 76%
“…The new-born rat has a mean arterial pressure of only about 14 mm Hg as compared with an adult pressure of 130 mm Hg. The various cardiovascular phenomena which are associated with one or the other type of muscle which have been studied so far, such as the high capillary density and high blood flow in slow muscle [3] and the greater flow response to exercise and adrenergic stimulation in the vasculature of fast muscle [4,5,6], may be only characteristic of the adult muscles. In the present experiments the relatively insensitive vascular smooth muscle cell in fast and slow muscle of the neonatal rat is another indication of the immaturity of the vasculature at birth.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations